The Discovery of a Buried Temple in Paestum: The Advantages of the Geophysical Multi-Sensor Application - Luigi Capozzoli; Ilaria Catapano; Gregory De Martino; Gianluca Gennarelli; Giovanni Ludeno; Enzo Rizzo; Francesco Soldovieri; Francesco Uliano Scelza; Gabriel Zuchtriegel (Remote Sensing, 2020)
Southern Italy is characterized by important archaeological sites developed during the pre-roman period. Among these, Paestum and Velia Archaeological Park, located in the Campania region, represents one of the most important and well-preserved sites of the Magna Graecia. During the last year, several unexpected archaeological findings have permitted the supposition of the presence of another undiscovered temple at Paestum, in a not yet investigated area of the site, close to the fortification walls (Western City Walls) of the ancient city and a few meters away from the gate of Porta Marina. To support this amazing hypothesis, the Paestum and Velia Archaeological Park and the National Research Council planned an accurate campaign of geophysical surveys, based on the combined use of Geomagnetic and Ground Penetrating Radar methodologies. The results of the geophysical surveys have effectively supported the detection of the temple, providing detailed information about its location and highlighting the geometry of the basement of the structure with high accuracy. The discovery sheds new light on the archaeological and architectonic history of the site and may represent one of the most relevant archaeological discoveries of the XXI century performed in Italy.